Electrode piece, electrode assembly and battery
By designing the current collector and active material layer of the electrode sheet to form appropriate convex parts, the problem of insufficient electrolyte during the charging and discharging of the battery is solved, and better electrolyte infiltration and battery safety is achieved.
Patent Information
- Application Number
- CN202510031017.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-08
AI Technical Summary
During the charging and discharging process of the battery, due to the expansion and extrusion of the electrode assembly, the electrolyte is insufficient and the infiltration is poor, which is prone to problems such as interface deterioration and circulation failure.
An electrode sheet is designed, which includes a current collector and an active material layer provided on the surface of the current collector. The particle size of the active material particles is within the range of 7 μm≤Dv90≤40 μm, and the height of the convex part is within the range of 3 μm≤H≤80 μm to form an appropriate convex part, improve the gap between the isolation film and the electrode sheet, and improve the electrolyte wetting effect.
By optimizing the structure of the electrode sheet, the wetting effect of the electrolyte is improved, the active material layer is stabilized, the risk of microcracks and powder loss is reduced, and the safety of the battery is improved and the circulation performance is improved.
Smart Images

Figure CN119833554A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a pole piece, an electrode assembly and a battery. Background Art
[0002] The charge and discharge cycle life is a key performance of the battery. In addition to optimizing and innovating the battery electrolyte to improve the charge and discharge cycle life, the charge and discharge cycle life can also be effectively improved by designing and improving the material and structure of the battery electrode. This puts more requirements on the design of the electrode. Summary of the invention
[0003] The inventors found that there would be extrusion between the layers of the electrode assembly, especially during the battery charging and discharging process, the expansion and extrusion of the electrode assembly would be further aggravated, resulting in insufficient electrolyte between the layers of the electrode assembly, poor wetting, prone to interface deterioration, and even abnormal conditions such as poor wetting and cycle failure.
[0004] The embodiments of the present application provide a pole piece, an electrode assembly and a battery, which can improve the problem of poor electrolyte infiltration in the battery.
[0005] In a first aspect, an embodiment of the present application provides a pole piece, the pole piece comprising a current collector and an active material layer disposed on a surface of the current collector;
[0006] The active material layer includes an active material, and the particle size Dv90 of the active material satisfies: 7 μm≤Dv90≤40 μm;
[0007] Part of the current collector and part of the active material layer of the pole piece protrude toward the same side to form a plurality of protrusions. In the thickness direction of the pole piece, the height of the protrusion is H, and H satisfies: 3μm≤H≤80μm.
[0008] Based on the pole piece of the embodiment of the present application, in the range of 7μm≤Dv90≤40μm, the particle size Dv90 of the active material is suitable, which is conducive to processing a convex portion with a good shape. In the range of 3μm≤H≤80μm, the height H of the convex portion is suitable, which can provide stable support for the isolation membrane, so that there is a suitable space between the pole piece and the isolation membrane for accommodating the electrolyte, and improving the electrolyte infiltration effect.
[0009] In some embodiments, the pole piece satisfies one of the following conditions:
[0010] (1)7μm≤Dv90≤20μm, 30μm <H≤80μm;
[0011] (2) 20 μm <Dv90≤40μm,3μm≤H≤30μm。
[0012] Based on the above embodiments, the particle size Dv90 of the active material and the height H of the convex portion can be more matched, making the active material layer more stable, less prone to microcracks and powder loss, and less side reactions at the convex portion, effectively improving the safety of battery use when the electrode is used in the battery.
[0013] In some embodiments, the coating weight per unit area of the active material layer is CW, and CW satisfies: 150 mg / 1540.25 cm 2 ≤CW≤400mg / 1540.25cm 2 .
[0014] Based on the above embodiments, the pole piece has a suitable electrolyte infiltration effect, and it is easy to control the thickness of the active material layer within a suitable range. Therefore, when the pole piece is raised to form a convex portion, the active material layer is not prone to microcracks, and the active material layer is not prone to abnormal situations such as powder loss and puncturing the isolation membrane.
[0015] In some embodiments, the pole piece satisfies one of the following conditions:
[0016] (1) 150mg / 1540.25cm 2 ≤CW≤210mg / 1540.25cm 2 , 3μm≤H1≤30μm;
[0017] (2) 210mg / 1540.25cm 2 <CW≤270mg / 1540.25cm 2 , 30μm
[0018] (3) 270mg / 1540.25cm 2 <CW≤400mg / 1540.25cm 2 , 40μm
[0019] Based on the above embodiments, CW and the height of the convex portion can be more closely matched, so that a convex portion with a suitable thickness H can be selected under a suitable coating weight CW, to prevent the coating weight CW from being within a certain range, where the height H of the convex portion is too small, and the supporting capacity of the convex portion is insufficient, making it difficult to meet the electrolyte infiltration requirements; and to prevent the coating weight CW from being within a certain range, where the height H of the convex portion is too large, and the elongation of the electrode at the convex portion is too large, resulting in the risk of microcracks on the surface of the active material layer, powder loss, and puncturing the diaphragm.
[0020] In some embodiments, the active material layer includes a binder. Based on the total weight of the active material layer, the weight percentage of the active material is La, the weight percentage of the binder is Lb, La satisfies: 94%≤La≤98.6%, and Lb satisfies: 0.3%≤Lb≤2%.
[0021] Based on the above embodiments, the adhesive can provide good adhesion, so that the active material particles and the active material and the collector surface have good adhesion, and then when part of the pole piece is raised to form a convex portion, the active material layer at the convex portion is not prone to microcracks and the active material layer is not prone to powdering.
[0022] In some embodiments, the pole piece satisfies at least one of the following conditions:
[0023] (1) 94% ≤ La ≤ 97.6%, 0.5% <Lb≤2%,40μm<H≤80μm;
[0024] (2) 94% ≤ La ≤ 97.6%, 0.3% <Lb≤0.5%,20μm<H≤40μm;
[0025] (3) 94%≤La≤97.6%, 0.1%≤Lb≤0.3%, 3μm≤H≤20μm;
[0026] (4) 97.6% <La≤98.6%,0.7%<Lb≤1.2%,40μm<H≤80μm;
[0027] (5) 97.6% <La≤98.6%,0.5%<Lb≤0.7%,20μm<H≤40μm;
[0028] (6) 97.6% <La≤98.6%,0.3%≤Lb≤0.5%,3μm≤H≤20μm;
[0029] (7) 98.6% <La≤99.2%,0.6%≤Lb≤1.2%,3μm≤H≤20μm。
[0030] Based on the above embodiments, it is convenient to select a protrusion of appropriate height under the corresponding active material and adhesive content to increase the supporting capacity of the protrusion. For the process of processing the protrusion, a higher protrusion height can be achieved while improving the processing efficiency of the protrusion and preventing the risk of short circuit, which significantly improves the battery efficiency and safety, thereby reducing the impact of the protrusion on the pole piece on the thermal safety and mechanical safety performance of the battery.
[0031] In some embodiments, in the thickness direction of the pole piece, the radius of the orthographic projection of the convex portion is R, wherein the convex portion has a sharpness S, S=H / R, and the pole piece satisfies at least one of the following conditions:
[0032] (1) R satisfies: 0 μm <R≤133μm;
[0033] (2) S satisfies: 0.4≤S≤0.6.
[0034] Based on the above embodiments, the convex portion has good support stability for the isolation membrane, the convex portion is not easily bent or deformed by external force, and the convex portion is not easy to cause damage to the isolation membrane.
[0035] In some embodiments, along the thickness direction of the pole piece, the radius of the orthographic projection of the convex portion is R, and the pole piece satisfies at least one of the following conditions:
[0036] (1) The center distance between two adjacent convex parts is L, 2≤L / R≤3;
[0037] (2) Within the unit area of the pole piece, the total area of the orthographic projection of the convex portion accounts for M, and 40%≤M≤80%.
[0038] Based on the above embodiments, it is convenient to select a suitable distribution density of the protrusions to prevent the protrusions from being too sparsely distributed and insufficient in supporting capacity, and to prevent the protrusions from being too densely distributed and obstructing the flow of the electrolyte.
[0039] In a second aspect, an embodiment of the present application provides an electrode assembly, which includes an isolation membrane and a plurality of pole pieces, wherein the isolation membrane is sandwiched between two pole pieces with opposite polarities, and at least one of the plurality of pole pieces adopts the above-mentioned pole piece.
[0040] In a third aspect, an embodiment of the present application provides a battery, comprising an outer package and the above-mentioned electrode assembly, wherein the electrode assembly is disposed in an internal space of the outer package.
[0041] Based on the pole piece, electrode assembly and battery of the embodiment of the present application, by selecting the particle size Dv90 of the active material to satisfy 7μm≤Dv90≤40μm, and selecting the height H of the protrusion to satisfy 3μm≤H≤80μm, the particle size Dv90 of the active material and the height H of the protrusion 311 are matched. On the basis of the height H being able to play a supporting role so that there is a suitable gap between the isolation membrane and the pole piece, and improving the electrolyte infiltration effect, a protrusion with a better shape can be processed, and the active material layer is not prone to abnormal conditions such as microcracks, powder loss or puncturing the separator, thereby improving the quality rate during the winding process. When the pole piece 300 is used in a battery, the battery can have good safety in use. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0043] Figure 1 This is a schematic diagram of the front view structure of a pole piece in an embodiment of the present application in an unfolded state;
[0044] Figure 2 This is a schematic cross-sectional structural diagram of an electrode assembly according to an embodiment of the present application;
[0045] Figure 3 This is a schematic diagram of a partial cross-sectional structure of a pole piece having a convex portion according to an embodiment of the present application;
[0046] Figure 4 This is a schematic diagram of the main structure of a pole piece having an end clearance area according to an embodiment of the present application;
[0047] Figure 5 This is a schematic diagram of the front view structure of a pole piece having a pole ear area according to an embodiment of the present application;
[0048] Figure 6 This is a schematic diagram of the main structure of a pole piece in which the pole ear area penetrates the pole piece in one embodiment of the present application.
[0049] Reference numerals:
[0050] 20. Electrode body; 21. Straight section; 22. Corner section; 100. Tab; 40. Tab assembly; 50. Isolation membrane;
[0051] 300, pole piece; 311, convex part;
[0052] 410, positive electrode sheet; 420, negative electrode sheet;
[0053] 310, convex point area; 320, ear area; 330, end avoidance area; 331, head avoidance area; 332, end avoidance area; 341, first area; 342, second area;
[0054] X, length direction; Y, width direction; Z, thickness direction. DETAILED DESCRIPTION
[0055] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0056] The inventors discovered that the electrode assembly inside the secondary battery adopts a winding structure, and the electrode assembly needs to be hot-pressed after the pole pieces and the isolation membranes are alternately stacked and wound. There is internal stress inside the electrode assembly, resulting in poor electrolyte wettability. In addition, the electrode assembly will expand during the charge and discharge process, and the interlayer extrusion of the electrode assembly will be further aggravated, resulting in insufficient electrolyte, poor wetting, and ultimately deterioration of the interface at the weak position, and even lithium deposition. In order to solve the above problems, it is necessary to create gaps between battery layers. Currently, there are the following methods for creating gaps: (1) sticking adhesive tape at specific positions of the electrode sheets to support the formation of gaps. This method currently improves the wetting ability, but the presence of the adhesive tape occupies the thickness, which increases the thickness of the electrode assembly and causes a certain loss in the energy density of the battery; (2) applying soluble chemicals to form gaps by evenly applying some glue soluble in electrolyte on the electrode sheets, but the improvement effect is limited and has other side effects on battery performance; (3) thickening the isolation membrane. The isolation membrane has a stronger ability to store electrolyte and improves the wetting effect of the electrolyte, but this method will make the battery thicker and greatly lose energy density.
[0057] The inventors also found that by machining a convex portion on the pole piece, the convex portion plays a supporting role during the winding process, so that a gap is formed between the pole piece layers of the electrode assembly, thereby improving the transmission capacity of the electrolyte inside the electrode assembly and improving the cycle performance of the battery. Based on this, the embodiment of the present application provides a pole piece, an electrode assembly and a battery, and the convex portion of the pole piece is designed to effectively improve the electrolytic infiltration and pole piece interface problems.
[0058] The battery provided in the embodiment of the present application includes an outer package and an electrode assembly disposed in the inner space of the outer package, and an electrolyte filled in the inner space of the outer package. The electrode assembly includes two pole pieces with opposite polarities and a separator, such as Figure 1 As shown, it is a schematic diagram of the main structure of an electrode sheet 300 in an embodiment of the present application in an unfolded state. The electrode sheets 300 have a length direction X, a width direction Y and a thickness direction Z that are perpendicular to each other. The length directions X, the width directions Y and the thickness directions Z of the two electrode sheets 300 with opposite polarities of the electrode assembly are consistent, as shown in FIG. Figure 2 As shown, the isolation film 50 is arranged between two pole sheets 300 with opposite polarities in the thickness direction Z of the pole sheets 300, one of the two pole sheets 300 with opposite polarities is a positive pole sheet 410, and the other is a negative pole sheet 420. The isolation film 50 has insulating properties and is used to separate the positive pole sheet 410 from the negative pole sheet 420 to prevent the positive pole sheet 410 and the negative pole sheet 420 from short-circuiting.
[0059] At least one of the positive electrode sheet 410 and the negative electrode sheet 420 has a convex portion 311. Specifically, the electrode sheet includes a current collector and an active material layer. The active material layer and the current collector are stacked along the thickness direction Z of the electrode sheet 300, and the active material layer is disposed on the surface of the current collector. The convex portion 311 is formed by a portion of the current collector and a portion of the active material layer protruding toward the same side of the electrode sheet 300 along the thickness direction Z of the electrode sheet 300. The convex portion 311 provides support for the isolation film 50, so that there is a gap between the isolation film 50 and the electrode sheet 300, and the electrolyte infiltration effect is improved.
[0060] It is understandable that part of the current collector and part of the active material layer need to be extended and deformed to form the convex portion 311, wherein the active material layer includes active materials. When the active material layer is extended, the particle size of the active material particles is likely to affect the morphological stability of the active material layer at the convex portion 311. For example, if the particle size of the active material particles is too large, it is easy to cause the active material layer at the convex portion 311 to have microcracks, powder loss or pierce the separator 50, etc., affecting the battery winding process. The superior rate and the safety of the battery. In addition, the larger the particle size of the active material, the smaller the contact area between the active material and the electrolyte, and the smaller the side reaction, but it leads to an increase in the diffusion path of ions inside the solid particles, reducing the kinetic performance of the electrode; the smaller the particle size of the active material, the shorter the diffusion path of ions inside the particles, but the specific surface area of the active material increases, resulting in an increase in the actual contact area between the active material and the electrolyte, so that the side reactions on the surface of the positive or negative active material particles increase, which is not conducive to the cycle stability of the battery.
[0061] In the embodiment of the present application, the particle size Dv90 of the active material satisfies: 7μm≤Dv90≤40μm. For example, Dv90 can be 7μm, 12μm, 18μm, 22μm, 28μm, 32μm, 40μm or any range of the above two. In the above particle size range, the particle size Dv90 of the active material is suitable, which is conducive to processing the convex portion 311 with good shape. In the thickness direction Z of the pole piece 300, such as Figure 3As shown, the height of the convex portion 311 is H, and H satisfies: 3μm≤H≤80μm. For example, H can be 3μm, 7μm, 12μm, 18μm, 22μm, 28μm, 32μm, 40μm or any range of the above two. In the above height range, the height H of the convex portion 311 is appropriate, which can provide stable support for the separator 50, so that there is a suitable space between the pole piece 300 and the separator 50 for accommodating the electrolyte, and improving the electrolyte infiltration effect. In the embodiment of the present application, by selecting the particle size Dv90 of the active material and the height H of the convex portion 311 to meet the range of the above conditional formula, the particle size Dv90 of the active material and the height H of the convex portion 311 are matched, and the convex portion 311 with a better shape can be processed, and the active material layer is not prone to abnormal conditions such as microcracks, powder loss or puncturing the diaphragm, thereby improving the superiority rate during the winding process. When the pole piece 300 is used in the battery, the battery can have good safety in use. When the particle size Dv90 of the active material is lower than 7 μm, the particle size of the active material is too small, which is easy to increase the side reaction. When the particle size Dv90 of the active material is higher than 40 μm, the particle size of the active material is too large, which is not conducive to the molding of the convex portion 311, and the surface of the active material layer is prone to microcracks, powder loss or piercing the isolation film 50. When H is higher than the upper limit of 80 μm, the height of the convex portion 311 is too high, and it is easy to be deformed by external force, and the elongation of the convex portion 311 is too large, which is easy to cause abnormal conditions such as microcracks and powder loss on the surface of the active material layer. When H is lower than the lower limit of 3 μm, the height of the convex portion 311 is too low, and it is not easy to provide stable support for the isolation film 50, and it is impossible to have a suitable space between the pole piece 300 and the isolation film 50 for accommodating the electrolyte, and the effect of improving the electrolyte infiltration cannot be achieved.
[0062] The pole piece 300 includes a first surface perpendicular to the thickness direction Z of the pole piece 300. Figure 1 The first surface includes a convex region 310, and a plurality of convex portions 311 are provided in the convex region 310, and there is a gap between the convex region 310 and the edge of the first surface. After the two pole pieces 300 and the isolation film 50 are wound multiple times to form the electrode body 20, the convex portion 311 contacts the isolation film 50 to provide support for the isolation film 50. When the electrode body 20 expands, the convex portion 311 can still support the isolation film 50. The contact area between the convex portion 311 and the isolation film 50 is small, so that there is space between the portion of the pole piece 300 corresponding to the convex region 310 and the isolation film 50 for accommodating electrolyte, thereby preventing abnormal situations such as insufficient electrolyte and poor wetting between the pole piece 300 and the isolation film 50 due to expansion and extrusion.
[0063] like Figure 2As shown, the isolation film 50 and the two pole pieces 300 are wound multiple times along the length direction X of the pole piece 300 to form the electrode body 20, and the length direction X of the pole piece 300 is the direction in which the pole piece 300 is wound. The electrode body 20 is flat, and the electrode body 20 includes a straight portion 201 and two corner portions 202, and the two corner portions 202 are arranged at opposite ends of the straight portion 201. Specifically, each circle of the pole piece 300 of the electrode body 20 includes two straight sections 21 and two corner sections 22, and the two straight sections 21 are arranged side by side in a direction perpendicular to the plate surface of the straight section 21, and the two corner sections 22 are arranged oppositely along the plate surface of the straight section 21, that is, the two straight sections 21 and the two corner sections 22 are connected end to end in sequence. The electrode body 20 has a tail end, and the tail end is formed by a part of the straight section 21 of the outermost circle of the pole piece 300. All the straight sections 21 stacked in a direction perpendicular to the surface of the straight section 21, the tail end and the isolation membrane 50 sandwiched between two adjacent straight sections 21 together form a straight portion 201; all the corner sections 22 located on the same side of the straight section 21 in a direction parallel to the surface of the straight section 21 and the isolation membrane 50 sandwiched between two adjacent corner sections 22 together form a corner portion 202.
[0064] The pole piece 300 has a plurality of convex portions 311, and at least one of the straight section 21 and the corner section 22 has a convex portion 311. Optionally, all the convex portions 311 provided on a single pole piece 300 protrude toward the same side of the pole piece 300 in the thickness direction Z of the pole piece 300. For example, when both the straight section 21 and the corner section 22 have convex portions 311, the convex portions 311 provided on the straight section 21 and the convex portions 311 provided on the corner section 22 both protrude toward one side of the winding center of the electrode body 20; or, the convex portions 311 provided on the straight section 21 and the convex portions 311 provided on the corner section 22 both protrude toward the side away from the winding center of the electrode body 20. Optionally, a portion of the protrusions 311 provided on a single pole piece 300 protrudes toward one side of the pole piece 300 in the thickness direction Z of the pole piece 300, and another portion of the protrusions 311 protrudes toward the other side of the pole piece 300 in the thickness direction Z of the pole piece 300. For example, the protrusions 311 provided on the straight section 21 protrude toward one side of the winding center of the electrode body 20, and the protrusions 311 provided on the corner section 22 protrude toward the side away from the winding center of the electrode body 20; or, the protrusions 311 provided on the straight section 21 protrude toward the side away from the winding center of the electrode body 20, and the protrusions 311 provided on the corner section 22 protrude toward the side of the winding center of the electrode body 20.
[0065] The above is only an exemplary introduction. The present application does not limit the orientation of the protrusion 311 of each pole piece 300 , and the orientation can be selected according to actual needs.
[0066] Due to the internal stress inside the electrode body 20 and the expansion of the electrode body 20 during the battery charging and discharging process, the two adjacent pole pieces 300 are easily squeezed, especially the corner sections 22 of the two adjacent pole pieces 300 are squeezed more strongly, and the gap is insufficient, resulting in poor electrolyte infiltration. Under the action of squeezing force and internal stress, when the corner section 22 has a convex portion 311, the convex portion 311 in the corner section 22 is prone to deformation and cracks in the active material layer, thereby affecting the cycle performance of the battery. By selecting the particle size Dv90 of the active material to satisfy 7μm≤Dv90≤40μm, and selecting the height H of the convex portion to satisfy 3μm≤H≤80μm, during the winding process of the pole piece 300, and when the convex portion 311 is subjected to squeezing force and internal stress, the convex portion 311 of the corner section 22 can maintain good support stability, and the active material layer at the corner section 22 can still maintain good morphological stability, and it is not easy to produce microcracks or powder falling.
[0067] In some embodiments, the pole piece 300 satisfies one of the following conditions:
[0068] (1)7μm≤Dv90≤12μm, 40μm <H≤80μm;
[0069] (2) 12 μm <Dv90≤20μm,30μm<H≤60μm;
[0070] (3) 20 μm <Dv90≤30μm,20μm<H≤40μm;
[0071] (4) 30 μm <Dv90≤40μm,3μm≤H≤20μm。
[0072] By selecting the particle size Dv90 of the active material and the height H of the protrusion 311 to satisfy the above range, the particle size Dv90 of the active material and the height H of the protrusion 311 can be more matched, making the active material layer more stable, less prone to microcracks and powder loss, and less side reactions at the protrusion 311, effectively improving the safety of battery use when the electrode 300 is used in the battery.
[0073] In some embodiments, the coating weight per unit area of the active material layer is CW, and CW satisfies: 150 mg / 1540.25 cm 2 ≤CW≤400mg / 1540.25cm 2 , for example, CW can be 150mg / 1540.25cm 2 、200mg / 1540.25cm 2 、280mg / 1540.25cm 2 、350mg / 1540.25cm 2, 400mg / 1540.25cm 2 By selecting the coating weight CW per unit area of the active material layer within the above range, the pole piece 300 has a suitable electrolyte infiltration effect, and it is easy to control the thickness of the active material layer within a suitable range, and then when the pole piece 300 is raised to form the convex portion 311, the active material layer is not prone to microcracks, and the active material layer is not prone to abnormal conditions such as powder shedding and piercing the isolation film 50.
[0074] It is understandable that for different coating weights per unit area CW, the required electrolyte wetting ability is different. For low CW pole pieces 300, the pole piece 300 thickness is small, and less electrolyte is required. At this time, the smaller height of the protrusion 311 can meet the battery wetting requirements. For higher CW pole pieces 300, the thickness of the pole piece 300 is greatly increased, and the amount of electrolyte required is greatly increased. If the smaller protrusion 311 design is still used, it cannot meet the actual needs of electrolyte wetting, and it will still cause uneven wetting inside the battery, resulting in problems such as battery purple spots and lithium precipitation. Similarly, for the pole piece 300 with a lower CW, if a larger height of the protrusion 311 is used, although the electrolyte infiltration requirements can be met, when the protrusion 311 structure is generated, stress and plastic deformation are generated on the pole piece 300. At this time, the pole piece 300 is extended. The higher the height H of the protrusion 311, the greater its elongation rate, the greater the damage to the pole piece 300, and it is more likely to produce microcracks on the surface of the active material layer, causing risks such as powder loss and puncturing the diaphragm, affecting the winding process and battery safety. Therefore, different CWs need to be matched with different protrusion 311 heights to achieve optimal infiltration without affecting the battery process and safety. Based on this, the embodiment of the present application selects the pole piece 300 to meet one of the following conditions:
[0075] (1) 150mg / 1540.25cm 2 ≤CW≤210mg / 1540.25cm 2 , 3μm≤H1≤30μm;
[0076] (2) 210mg / 1540.25cm 2 <CW≤270mg / 1540.25cm 2 , 30μm
[0077] (3) 270mg / 1540.25cm 2 <CW≤400mg / 1540.25cm 2 , 40μm
[0078] By selecting the coating weight CW per unit area of the active material layer and the height of the protrusion 311 to satisfy the range of the above conditional formula, CW and the height of the protrusion 311 can be more closely matched, so that the protrusion 311 with a suitable thickness H can be selected under the condition of a suitable coating weight CW, to prevent the height H of the protrusion 311 from being too small when the coating weight CW is within a certain range, and the supporting capacity of the protrusion 311 is insufficient to meet the electrolyte infiltration requirements, resulting in uneven internal infiltration of the battery; and to prevent the height H of the protrusion 311 from being too large when the coating weight CW is within a certain range, and the elongation of the pole piece 300 at the protrusion 311 is too large, resulting in the risk of microcracks on the surface of the active material layer, powder loss, and puncture of the diaphragm.
[0079] In some embodiments, the active material mainly provides ions or stores ions during the charge and discharge process, and the active material layer also includes a binder, which plays a role in bonding and fixing all active materials, so that all active material layers become a whole and are bonded to the surface of the current collector. Based on the total weight of the active material layer, the weight percentage of the active material is La, and the weight percentage of the binder is Lb, wherein La satisfies: 94%≤La≤98.6%, and Lb satisfies: 0.3%≤Lb≤2.0%. For example, La can be 94%, 94.5%, 95.0%, 96.3%, 97.4%, 98.6% or any range of the above two, and Lb can be 0.3%, 0.8%, 1.2%, 1.5%, 1.8%, 2.0% or any range of the above two. By selecting the weight percentage La of the active material and the weight percentage Lb of the adhesive to satisfy the range of the above conditional formula, the adhesive can provide good adhesion, so that the active material particles and the active material and the surface of the collector have good adhesion, and then when part of the pole piece 300 is raised to form a convex portion 311, the active material layer at the convex portion 311 is not easy to produce microcracks, and the active material layer is not easy to fall off.
[0080] It is understandable that different active material contents or different adhesive contents have different stresses and plastic deformation capabilities on the pole piece 300. The higher the active material content Lb, the lower the adhesive content, and the more likely the active material is to fall off during the manufacturing process of the convex portion 311. Different pole pieces 300 need to use different convex portion 311 heights according to the active material content La and the adhesive content Lb. Based on this, the embodiment of the present application selects the pole piece 300 to meet one of the following conditions:
[0081] (1) 94% ≤ La ≤ 97.6%, 0.5% <Lb≤2%,40μm<H≤80μm;
[0082] (2) 94% ≤ La ≤ 97.6%, 0.3% <Lb≤0.5%,20μm<H≤40μm;
[0083] (3) 94% ≤ La ≤ 97.6%, 0.1% ≤ Lb ≤ 0.3%, 3 μm ≤ H ≤ 20 μm;
[0084] (4) 97.6% < La ≤ 98.6%, 0.7% < Lb ≤ 1.2%, 40 μm < H ≤ 80 μm;
[0085] (5) 97.6% < La ≤ 98.6%, 0.5% < Lb ≤ 0.7%, 20 μm < H ≤ 40 μm;
[0086] (6) 97.6% < La ≤ 98.6%, 0.3% ≤ Lb ≤ 0.5%, 3 μm ≤ H ≤ 20 μm;
[0087] (7) 98.6% < La ≤ 99.2%, 0.6% ≤ Lb ≤ 1.2%, 3 μm ≤ H ≤ 20 μm.
[0088] By selecting the weight percentage La of the active material and the weight percentage Lb of the binder to satisfy the ranges of the above conditional expressions, it is convenient to select the convex portion 311 with a suitable height under the corresponding active material and binder contents, increase the supporting ability of the convex portion 311. For the process of processing the convex portion 311, it is possible to achieve a higher height of the convex portion 311 while improving the processing yield rate of the convex portion 311, preventing the risk of short circuit, significantly improving the battery yield rate and safety, and further reducing the influence of the convex portion 311 existing on the pole piece 300 on the thermal safety and mechanical safety performance of the battery, while improving the battery wetting and the charge and discharge cycle performance of the battery.
[0089] In some embodiments, as Figure 3 shown, in the thickness direction of the pole piece 300, the radius of the orthographic projection of the convex portion 311 is R, and R satisfies: 0 μm < R ≤ 133 μm. For example, R can be 20 μm, 45 μm, 83 μm, 103 μm, 120 μm, 133 μm or any range between the two. By selecting the radius R of the orthographic projection of the convex portion 311 to satisfy the range of the above conditional expression, it is convenient to select the size of the convex portion 311 within a suitable range. The convex portion 311 has a good supporting effect and is not easily deformed. At the same time, it is convenient to select a suitable area ratio of the convex portion 311 relative to the pole piece 300, which can provide more sufficient support for the separator 50.
[0090] In some embodiments, the convex portion 311 has a sharpness S, S=H / R, S satisfies: 0.4≤S≤0.6, for example, S can be 0.40, 0.45, 0.48, 0.50, 0.54, 0.60 or any range of the above two. By selecting the range in which the sharpness S of the convex portion 311 satisfies the above conditional expression, the convex portion 311 has good support stability for the isolation membrane 50, the convex portion 311 is not easily bent or deformed by external force, and the convex portion 311 is not easy to damage the isolation membrane 311. When the particle size Dv90 of the active material satisfies 7μm≤Dv90≤40μm, the processing rate of the convex portion 311 can be improved, so that the active material layer is not easy to produce microcracks and is not easy to lose powder.
[0091] In some embodiments, the center distance between two adjacent protrusions 311 is L, 2≤L / R≤3, for example, L / R can be 2.0, 2.2, 2.4, 2.6, 2.8, 3.0 or any range of the above two. By selecting the range where the center distance L between two adjacent protrusions 311 and the radius R of the positive projection of the protrusion 311 meet the above conditional expression, it is convenient to select a suitable distribution density of the protrusions 311, prevent the protrusions 311 from being too sparsely distributed and insufficient in supporting capacity, and prevent the protrusions 311 from being too densely distributed and hindering the flow of the electrolyte.
[0092] In some embodiments, within the unit area of the pole piece 300, the total area of the orthographic projection of the convex portion 311 accounts for M, 40%≤M≤80%, for example, M can be 40%, 44%, 50%, 55%, 60%, 80% or any range of the above two. By selecting the total area of the orthographic projection of the convex portion 311 to account for M in the range that satisfies the above conditional expression, the convex portion 311 can provide more sufficient support for the isolation film 50. At the same time, when the particle size Dv90 of the active material satisfies 7μm≤Dv90≤40μm, the processed convex portion 311 has a complete shape, and the active material layer is not prone to microcracks or powder loss.
[0093] In some embodiments, the surface of the active material layer facing away from the current collector forms a first surface, and the convex portion 311 is provided in the convex region 310 of the first surface, and the convex region 310 is defined by the convex boundary line. The convex portion 311 of the convex region 310 may be located in the inner area defined by the convex boundary line, and the convex portion 311 may also be inscribed in the convex boundary line. The first surface also includes an end avoidance region 330 and an edge avoidance region. The end avoidance region 330 is connected to the end of the convex region 310 in the length direction X of the pole piece 300 and extends to the edge of the pole piece 300. The edge avoidance region is provided on one side of the convex region 310 in the width direction Y of the pole piece 300 and extends to the edge of the pole piece 300. The convex portion 311 is not provided in the edge avoidance region and the end avoidance region 330. After the two pole pieces 300 and the isolation film 50 are wound, the surface of the pole piece 300 corresponding to the edge avoidance region and the end avoidance region 330 can be spaced from the isolation film 50.
[0094] The end avoidance region 330 is disposed at the end of the convex point region 310 in the length direction X of the pole piece 300 and extends to the edge of the pole piece 300, and the end avoidance region 330 also extends to the edge of the pole piece 300 in the width direction Y of the pole piece 300. Figure 4 As shown, the end space avoidance area 330 includes at least one of a head space avoidance area 331 and a tail space avoidance area 332. Preferably, the end space avoidance area 330 includes both the head space avoidance area 331 and the tail space avoidance area 332. In the length direction X of the pole piece 300, the head space avoidance area 331 is arranged at one end of the convex point area 310, and the tail space avoidance area 332 is arranged at the other end of the convex point area 310.
[0095] After the two pole pieces 300 and the isolation film 50 are wound, the head air avoidance area 331 can be located in the innermost turns of the electrode body 20, which is convenient for the winding of the electrode body 20 and helps to improve the structural stability of the central area of the electrode body 20. The tail air avoidance area 332 can be located in the outermost turns of the electrode body 20. The tail air avoidance area 332 can serve as a buffer area between the protrusion 311 and the tail end of the electrode body 20, so that the portion of the pole piece 300 corresponding to the end air avoidance area 330 can more smoothly form a constraint on the inner layer structure of the electrode body 20, which helps to improve the packaging stability of the electrode body 20. Especially when the electrode body 20 has a tendency to expand, the tail air avoidance area 332 without the protrusion 311 is used for tailing, which can prevent the tail of the electrode body 20 from slipping due to expansion stress and improve the structural stability of the electrode body 20.
[0096] The edge avoidance area includes a first area 341 and a second area 342. In the width direction Y of the pole piece 300, the first area 341 is connected to one side of the convex area 310, and the second area 342 is connected to the other side of the convex area 310. The first area 341 extends to the edge of the pole piece 300 in a direction away from the second area 342, and the second area 342 extends to the edge of the pole piece 300 in a direction away from the first area 341. That is, the two opposite boundaries of the convex area 310 in the width direction Y of the pole piece 300 are respectively spaced from the corresponding edges of the pole piece 300, thereby preventing the deformation stress when the convex portion 311 is processed in the convex area 310 from causing abnormal deformation such as wavy edges or wrinkles on the edge of the pole piece 300.
[0097] Optionally, one of the first region 341 and the second region 342 is used to mount the tab assembly 40 of the electrode assembly, such as Figure 4 As shown, exemplarily, the second region 342 is used to mount the tab assembly 40 of the electrode assembly, and the convex region 310 is spaced apart from the tab assembly 40 .
[0098] Alternatively, if Figure 5 As shown, the first surface further includes a tab region 320, which extends from one edge of the first surface to the other opposite edge along the width direction Y of the pole piece 300 and does not penetrate the bump region 310. The tab region 320 is used to install the tab assembly 40 of the electrode assembly, and the tab assembly 40 is spaced apart from the bump region 310. In some other embodiments, such as Figure 6 As shown, the tab area 320 penetrates the convex point area 310 along the width direction Y of the pole piece 300. Each tab area 320 is used to set at least one tab assembly 40. For example, the tab assembly 40 includes a tab and a protective glue, and the tab and the protective glue can be installed in the same tab area 320; or, the tab is installed in one of the tab areas 320, and the protective glue is installed in another tab area 320.
[0099] The electrode sheet 300 of the embodiment of the present application can form at least one of the positive electrode sheet 410 and the negative electrode sheet 420. The current collector of the negative electrode sheet 420 is a negative electrode current collector and the active material layer is a negative electrode active material layer. The current collector of the positive electrode sheet 410 is a positive electrode current collector and the active material layer is a positive electrode active material layer. The embodiment of the present application has no particular restrictions on the materials of the positive electrode active material, the positive electrode current collector, the negative electrode active material and the negative electrode current collector. Various materials known in the art that can be used as positive electrode active materials, positive electrode current collectors, negative electrode active materials and negative electrode current collectors are applicable to the present application.
[0100] For example, the negative electrode current collector may be at least one of copper foil, aluminum foil, nickel foil or carbon-based current collector; the thickness of the negative electrode current collector may be 1 μm to 200 μm. The negative electrode active material layer may be disposed on one surface or two opposite surfaces of the negative electrode current collector. Further, in the thickness direction Z of the negative electrode sheet 420, the negative electrode active material layer may be coated only on a partial area of the negative electrode current collector. For example, the thickness of the negative electrode active material layer may be 10 μm to 500 μm.
[0101] Exemplarily, the negative electrode active material includes at least one of lithium metal, natural graphite, artificial graphite or silicon-based materials, and the silicon-based material includes at least one of silicon, silicon oxide, silicon carbon compound or silicon alloy. The negative electrode active material layer may also include a conductive agent, and exemplarily, the conductive agent in the negative electrode active material layer may include at least one of carbon black, acetylene black, Ketjen black, flake graphite, graphene, carbon nanotubes, carbon fibers or carbon nanowires. Among them, the negative electrode active material layer may also include a binder, and the binder may include at least one of carboxymethyl cellulose CMC, polyacrylate, polyacrylate, polyvinyl pyrrolidone, polyaniline, polyimide, polyamide-imide, polysiloxane, epoxy resin, polyester resin, polyurethane resin or polyfluorene.
[0102] For example, the positive electrode current collector may be made of aluminum foil, and of course, other positive electrode current collectors commonly used in the art may also be used, and the thickness of the positive electrode current collector may be 1 μm to 200 μm. The positive electrode active material layer may be disposed on one surface or two opposite surfaces of the positive electrode current collector, and further, in the thickness direction Z of the positive electrode sheet 410, the positive electrode active material layer may be coated only on a partial area of the positive electrode current collector, and the thickness of the positive electrode active material layer may be 10 μm to 500 μm.
[0103] For example, the positive electrode active material includes LiCoO2, LiNiO2, LiMn2O4, LiCo 1-y M y O2、LiNi 1-y M y O2、LiMn 2-y M y O4、LiNi x Co y Mn z M 1-x-y-zO2, wherein M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V or Ti, and 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1. Exemplarily, the positive electrode active material may include at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide or lithium nickel manganese oxide, and the above positive electrode active material may be doped and / or coated. The positive electrode active material layer also includes a conductive agent, and exemplarily, the conductive agent in the positive electrode active material layer may include at least one of conductive carbon black, acetylene black, Ketjen black, flake graphite, graphene, carbon nanotubes or carbon fibers. Among them, the positive electrode active material layer may also include a binder, and the binder may include at least one of a copolymer of vinylidene fluoride and hexafluoropropylene, a styrene-acrylate copolymer, a styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene.
[0104] The embodiments of the present application have no particular restrictions on the isolation membrane 50, and various materials known in the art that can be used as the isolation membrane 50 are applicable to the present application. Exemplarily, the isolation membrane 50 includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. Especially polyethylene and polypropylene, they have a good effect on preventing short circuits and can improve the stability of the electrode assembly through the shutdown effect. The thickness of the isolation membrane 50 is in the range of about 3μm to 500μm. The positive and negative ears are made of metal conductive materials.
[0105] The tabs in the embodiments of the present application include positive tabs and negative tabs. The positive tabs are arranged on the positive electrode sheet, and the negative tabs are arranged on the negative electrode sheet. The embodiments of the present application have no special restrictions on the positive tabs, negative tabs and protective glue. Various materials that can be used as positive tabs, negative tabs and protective glue known in the art are applicable to the present application.
[0106] The embodiments of the present application do not have any particular restrictions on the electrolyte. Various materials that can be used as electrolytes known in the art are applicable to the present application. The electrolyte includes lithium salts and non-aqueous organic solvents.
[0107] Illustratively, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium nitrate, and lithium methylsulfite.
[0108] Exemplarily, the non-aqueous organic solvent may also include at least one of a carboxylate compound, an ether compound or other organic solvent. The above-mentioned carbonate compound may include but is not limited to at least one of a chain carbonate compound and a cyclic carbonate compound. The above-mentioned chain carbonate compound may include but is not limited to at least one of dipropyl carbonate (DPC) or ethyl methyl carbonate (EMC). The above-mentioned cyclic carbonate compound may include but is not limited to at least one of butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate or propyl propionate. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate. The present application has no particular restrictions on the mass percentage of the non-aqueous organic solvent in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the total mass of the electrolyte, the mass percentage of the non-aqueous organic solvent is 10% to 70%.
[0109] The present application has no particular limitation on the battery packaging bag, which may be any packaging bag known in the art, as long as the purpose of the present application can be achieved.
[0110] The present application does not particularly limit the type of battery, which may include any device that generates an electrochemical reaction. In the present application, the battery may include but is not limited to: a lithium metal battery, a lithium ion battery, a lithium polymer battery or a lithium ion polymer battery, etc.
[0111] The preparation process of the battery of the present application is well known to those skilled in the art, and the present application has no special limitation. For example, it may include but is not limited to the following steps: after installing the positive electrode ear on the positive electrode sheet and the negative electrode ear on the negative electrode sheet, the positive electrode sheet, the isolation film and the negative electrode sheet are stacked in sequence, and they are wound, folded, etc. as needed to obtain an electrode assembly with a wound structure, the electrode assembly is placed in a packaging bag, the electrolyte is injected into the packaging bag and the bag is sealed to obtain a battery; or, the positive electrode sheet, the isolation film and the negative electrode sheet are stacked in sequence, and the four corners of the entire stacked structure are fixed with tape to obtain an electrode assembly with a stacked structure, the electrode assembly is placed in a packaging bag, the electrolyte is injected into the packaging bag and the bag is sealed to obtain a battery.
[0112] The battery of the present application can be used for an electrical device, and the present application does not particularly limit the type of the electrical device, and it can be used for any electrical device known in the prior art. In some embodiments, the electrical device may include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor, etc.
[0113] The present application is further described below by taking a lithium-ion battery as an example and combining specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.
[0114] The following methods are used to test the performance of lithium-ion batteries in various embodiments and comparative examples of the present application:
[0115] (1) Cyclic capacity retention rate test method at 25℃ / 45℃ 5C charge / 0.7C discharge
[0116] In a 25℃ / 45℃ environment, the lithium-ion battery is charged at a constant current of 5C to the full charge voltage (the maximum design voltage of the lithium-ion battery is 4.5V), and then charged at a constant voltage at the maximum voltage until the current is 0.02C, and then discharged at a constant current of 0.7C until the final voltage is 3.0V, and the discharge capacity of the first cycle is recorded. After that, the above steps are repeated for charging and discharging cycles, and the discharge capacity of the lithium-ion battery of each charge and discharge cycle is recorded.
[0117] 25°C / 45°C 5C charge / 0.7C discharge cycle capacity retention rate = (discharge capacity of the Nth cycle / discharge capacity of the first cycle) × 100%.
[0118] The number of cycles for 25℃ / 45℃5C cycle capacity ≤80% is: the number of charge and discharge cycles when the cycle capacity retention rate is 80%.
[0119] (2) Liquid retention test method
[0120] During the assembly process of lithium-ion batteries, after drying in a vacuum oven at 85°C for 12 hours to remove moisture, the weight of the dry battery before injection is calculated and recorded as w1; after the lithium-ion battery is obtained through vacuum packaging, standing, formation, capacity, degassing, trimming and other processes, the weight of the lithium-ion battery is calculated and recorded as w2.
[0121] Liquid retention amount = (w2-w1) / w1×100%.
[0122] (3) Wetting improvement effect test method
[0123] The electrode 300 was cut into a standard size of 10 mm × 10 mm, 5 μL of electrolyte was dripped on the surface of the electrode 300, the diffusion speed and wetting area of the electrolyte were observed, and the contact angle of the electrolyte on the surface of the electrode 300 was measured using a contact angle meter. The wettability of the electrode 300 was evaluated based on the diffusion speed and contact angle of the electrolyte. The faster the diffusion speed, the smaller the contact angle and the better the wettability.
[0124] Among them, the contact angle range is 15°~25°, the surface wetting effect is "good", and the contact angle range is 5°~15°, the surface wetting effect is "poor".
[0125] (4) Active material layer morphology test method
[0126] The pole piece 300 is cut into a standard size of 10 mm×10 mm, placed in a sample chamber of a scanning electron microscope (SEM), and the surface morphology of the pole piece 300 is observed using a scanning electron microscope (SEM).
[0127] If the surface of the pole piece 300 is smooth, complete and without cracks, there is no powder loss; if the number of pits per square centimeter on the surface of the pole piece 300 is less than or equal to 3, it means that the integrity of the pole piece 300 has been damaged, which is a slight powder loss; if the number of pits per square centimeter on the surface of the pole piece 300 is greater than 3, it means that the pole piece 300 has been severely damaged, which is a serious powder loss.
[0128] (5) Method for testing the height H of the protrusion 311
[0129] Take the pole piece 300 at the corner of the battery to test the height of the protrusion 311.
[0130] (6) Active material particle size Dv90 test method
[0131] The particle size Dv90 test is measured by a particle size analyzer. Dv90 means that 90% of the particle volume is less than the particle size of this value. It is necessary to take a representative sample from the material to be tested and select a suitable dispersion medium (such as water, ethanol, etc.) to ensure that the sample can be fully dispersed in the medium. Then use an ultrasonic disperser to treat the sample to break up the agglomerated particles. Inject the dispersed sample into the sample pool of the particle size analyzer. Start the instrument for measurement. The instrument will determine the particle size distribution of the particles by laser diffraction or dynamic light scattering, automatically collect data and generate a particle size distribution curve. Read the Dv90 value from the particle size distribution curve, that is, the particle size with 90% of the particle volume less than this value. Perform multiple measurements as needed to ensure the repeatability and accuracy of the results.
[0132] (7) Test method for coating weight per unit area of active material layer
[0133] Take a certain area of the electrode and cut it into discs with an area of 15.4025cm2 using a punching machine. After deducting the weight of the current collector, the coating weight per unit area of the active material layer can be obtained;
[0134] Example 1-1
[0135] (1) Preparation of positive electrode sheet
[0136] The positive electrode active material LiCoO2, the positive electrode conductive agent conductive carbon black (Super P), the positive electrode binder polyvinylidene fluoride (PVDF, Mw = 7 × 10 6 ) are mixed in a mass ratio of 97.5:1:1.5, N-methylpyrrolidone (NMP) is added as a solvent, and stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 75wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried and cold pressed at 85°C to obtain a positive electrode sheet with a single-sided coating of a positive electrode active material layer with a thickness of 50μm. After that, the above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided coating of a positive electrode active material layer. Then, the positive electrode sheet with a specification of 74mm×851mm is cut into pieces for standby use.
[0137] (2) Preparation of negative electrode sheet
[0138] The negative electrode active material artificial graphite, the negative electrode conductive agent conductive carbon black (Super P), the thickener carboxymethyl cellulose (CMC-Na, Mw = 7 × 10 5 ), negative electrode binder styrene butadiene rubber (SBR, Mw = 5 × 10 6 ) are mixed in a mass ratio of 97.5:1:0.5:1, and then deionized water is added as a solvent, and stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 50wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 8μm, and dried and cold pressed at 85°C to obtain a negative electrode sheet with a negative electrode active material layer coated on one side with a thickness of 60μm. Thereafter, the above steps are repeated on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode active material layer coated on both sides. Then, the negative electrode sheet with a specification of 76mm×867mm is cut into pieces for standby use, and the compaction density of the negative electrode active material layer is 1.75g / cm 3 The coating weight per unit area of the negative electrode active material layer is 230 mg / 1540.25 cm 2 , the particle size Dv90 of the negative electrode active material is 45μm.
[0139] (3) Preparation of isolation membrane
[0140] A polyethylene (PE) porous membrane with a thickness of 5 μm was used.
[0141] (4) Preparation of electrolyte
[0142] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a mass ratio of 1:1:2 to obtain a base solvent, and then lithium hexafluorophosphate (LiPF6) was dissolved in the above base solvent to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage of LiPF6 is 12.5%.
[0143] (5) Assembly of lithium-ion batteries
[0144] The positive electrode aluminum tab is installed on the edge area of the positive electrode sheet 410 by rolling, the protective adhesive is attached to the edge area of the positive electrode sheet 410, and the negative electrode nickel tab is installed on the edge area of the negative electrode sheet 420 by rolling.
[0145] The positive electrode sheet 410 with the positive electrode ear, the separator 50, and the negative electrode sheet 420 with the negative electrode ear are stacked in order, so that the separator 50 is located between the positive electrode sheet 410 and the negative electrode sheet 420 to play a role of isolation, and then wound to obtain the electrode body 20. The electrode assembly is placed in an outer packaging aluminum plastic film, placed in an 85°C vacuum oven for 12 hours to remove moisture, and then injected with electrolyte. After vacuum packaging, standing, formation (0.2°C constant current charging to 3.5V, and then 1C constant current charging to 3.9V), capacity, degassing, trimming and other processes, a lithium-ion battery is obtained.
[0146] In Example 1-1, the negative electrode sheet has a protrusion 311, and the protrusion is rolled out on the negative electrode sheet by rolling. Figure 4 The pole piece 300 shown is used as a negative pole piece, and in the electrode body 20 formed by winding, the corner section 21 and the straight section 22 of each circle of the pole piece 300 have a convex portion 311. The parameters of the lithium-ion battery are shown in Table I.
[0147] Table I
[0148] parameter Numeric parameter Numeric H 10μm R 80μm CW <![CDATA[230mg / 1540.25cm 2 ]]> L 160μm S 0.13 M 60% L / R 2.0 Lb 1.0% La 97.5%
[0149] Examples 1-2 to 1-25 and Comparative Examples 1-1 to 1-7 are the same as Example 1-1 except that the height of the protrusion 311 and the particle size Dv90 of the positive electrode active material are adjusted as shown in Table 1 during the preparation of the positive electrode sheet.
[0150] The parameters of the lithium-ion batteries of Examples 1-1 to 1-25 and Comparative Examples 1-1 to 1-7 and the performance test results of the lithium-ion batteries are shown in Table 1.
[0151] Table 1
[0152]
[0153]
[0154] Among them, the greater the number of charge and discharge cycles and the greater the liquid retention, the better the battery performance.
[0155] It can be seen from Examples 1-1 to 1-25 and Comparative Examples 1-1 to 1-7 in Table 1 that the particle size Dv90 of the active material satisfies 7μm≤Dv90≤40μm, and the height of the protrusion 311 satisfies 3μm≤H≤80μm, and the lithium ion battery has good charge and discharge cycle performance.
[0156] It can be seen from Examples 1-1 to 1-25 and Comparative Examples 1-1 to 1-7 in Table 1 that, within a certain range, although increasing the height of the protrusion 311 can improve wettability and increase the amount of liquid retained, when it exceeds the limit value, it will cause problems such as powdering, cracking or wrinkling of the electrode 300. At this time, although the electrode 300 still has improved wettability, problems such as powdering and cracking of the electrode 300 will lead to deterioration of the cycle performance.
[0157] When the height of the protrusion 311 is kept constant, the Dv90 of the active material cannot be too large. A too large Dv90 will cause the active material itself to be subjected to excessive stress and strain during the process of preparing the protrusion 311 of the electrode, thereby causing excessive interaction force with other particles in the electrode 300, resulting in falling off from the electrode 300, or even the breakage of the active particles themselves. At this time, although the wettability of the electrode 300 is still greatly improved, it is very unfavorable to the circulation of the electrode 300.
[0158] Examples 2-1 to 2-18 are the same as Example 1-7 except that the height H of the protrusion 311 and the protrusion weight CW per unit area of the positive electrode active material layer are adjusted as shown in Table 1 during the preparation of the positive electrode sheet.
[0159] The parameters of the lithium-ion batteries of Examples 2-1 to 2-18 and the performance test results of the lithium-ion batteries are shown in Table 2.
[0160] Table 2
[0161]
[0162]
[0163] It can be seen from Examples 2-1 to 2-3 in Table 2 that the weight CW of the protrusion per unit area of the active material layer and the height H of the protrusion 311 satisfy 150 mg / 1540.25 cm 2 ≤CW≤210mg / 1540.25cm 2 , 3μm≤H1≤30μm; According to Examples 2-4 to 2-9 in Table 2, it can be seen that the weight CW of the convex portion per unit area of the active material layer and the height H of the convex portion 311 meet 210mg / 1540.25cm 2 <CW≤270mg / 1540.25cm 2 , 30μm 2 <CW≤400mg / 1540.25cm 2 , 40μm
[0164] Examples 3-1 to 3-37 are the same as Example 2-5 except that the height H of the protrusion 311, the weight percentage Lb of the positive electrode active material and the weight percentage Lb of the binder are adjusted as shown in Table 1 during the preparation of the positive electrode sheet.
[0165] The parameters of the lithium-ion batteries of Examples 3-1 to 3-37 and the performance test results of the lithium-ion batteries are shown in Table 3.
[0166] Table 3
[0167]
[0168]
[0169] It can be seen from Examples 3-15, 3-20 to 3-49 in Table 3 that when the proportion of low-active materials is low and the content of the binder is low, it is very easy for particles to fall off and the electrode sheet 300 to rupture during the preparation of the convex portion 311, which is not conducive to improving the cycle stability. Therefore, when the content of low-active materials is low, a relatively high binder content should be maintained to facilitate the integrity of the electrode sheet 300 during the preparation of a relatively high convex portion 311, prevent particle shedding, and thus improve the wettability and cycle stability. When the proportion of the active material content further increases and reaches a medium level, the binder content can be appropriately reduced, and this will not affect the manufacturing process of the convex portion 311. If the active material content remains at a high level, the height of the convex portion 311 should be minimized because an increase in the proportion of the active material content means a relatively low binder content. In this case, if a relatively high height of the convex portion 311 is still maintained, powder falling due to weak bonding of the active particles and rupture of the electrode sheet 300 may occur during the preparation of the convex portion 311. Therefore, the active material content, the binder content, and the height of the convex portion 311 should be designed within the ranges defined by the above conditional expressions.
[0170] Examples 4-1 to 4-14 are the same as Examples 1-7 except that in the preparation of the positive electrode sheet, the height H of the convex portion 311, the positive projection radius R of the convex portion 311, and the center distance L between two adjacent convex portions 311 are adjusted according to Table 1.
[0171] The parameters of the lithium-ion batteries and the performance test results of the lithium-ion batteries in Examples 4-1 to 4-14 are shown in Table 4.
[0172] Table 4
[0173]
[0174] It can be seen from Examples 4-1 to 4-14 and Examples 1-7 in Table 4 that when the height H of the convex portion 311 is the same, the larger the positive projection radius R, the higher the liquid retention amount of the electrolyte and the better the wettability, indicating that a larger positive projection radius can significantly improve the electrochemical performance of the battery and further enhance the cycle performance. In addition, when the height H of the convex portion 311 is the same, the smaller the center distance L between two adjacent convex portions 311, the more conducive it is to improving the wettability and liquid retention amount of the electrolyte, and thus to enhancing the cycle performance. Therefore, when the design of the battery convex portion 311 satisfies at least one of 0μm < R ≤ 133μm, 0.4 ≤ S ≤ 0.6, and 2 ≤ L / R ≤ 3, while ensuring no powder falling and no rupture of the electrode sheet 300, increasing the size of the positive projection radius R of the convex portion 311 as much as possible and reducing the center distance between two adjacent convex portions 300 will have a better effect on improving the performance of the lithium-ion battery.
[0175] Embodiments 5-1 to 5-6 are the same as Embodiments 1-7 except that the height H of the protrusion 311 and the total area ratio M of the orthographic projection of the protrusion 311 per unit area are adjusted as shown in Table 1 during the preparation of the positive electrode sheet.
[0176] The parameters of the lithium-ion batteries of Examples 5-1 to 5-6 and the performance test results of the lithium-ion batteries are shown in Table 5.
[0177] Table 5
[0178]
[0179] It can be seen from Examples 5-1 to 5-6 and Examples 1-7 in Table 5 that, when the height H of the protrusion 311 is the same, the total area proportion M of the orthographic projection of the protrusion 311 per unit area satisfies 40%≤M≤80%. As M increases, the liquid retention amount of the charge and discharge cycle performance of the lithium-ion battery gradually increases, and the performance improvement effect on the lithium-ion battery is better.
[0180] The same or similar numbers in the drawings of this embodiment correspond to the same or similar parts; in the description of this application, it should be understood that if the terms "upper", "lower", "left", "right", etc. indicate an orientation or position relationship based on the orientation or position relationship shown in the drawings, it is only for the convenience of describing this application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as a limitation on this patent. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.
[0181] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A pole piece, characterized in that: The electrode tab includes a current collector and an active material layer disposed on the surface of the current collector; The active material layer includes active material, and the particle size Dv90 of the active material satisfies: 7μm ≤ Dv90 ≤ 40μm; Part of the current collector of the electrode tab and the active material layer on its surface protrude towards the same side to form a plurality of convex portions. Along the thickness direction of the electrode tab, the height of the convex portion is H, and H satisfies: 3μm ≤ H ≤ 80μm.
2. The pole piece according to claim 1, characterized in that: 7μm ≤ Dv90 ≤ 20μm, 30μm < H ≤ 80μm; or 20μm < Dv90 ≤ 40μm, 3μm ≤ H ≤ 30μm.
3. The pole piece according to claim 1, characterized in that: The coating weight per unit area of the active material layer is CW, and CW satisfies: 150 mg / 1540.25 cm 2 ≤CW≤400mg / 1540.25cm 2 .
4. The pole piece according to claim 3, characterized in that: The electrode tab satisfies one of the following conditions: (1)150mg / 1540.25cm 2 ≤CW≤210mg / 1540.25cm 2 ,3μm≤H1≤30μm; (2)210mg / 1540.25cm 2 <CW≤270mg / 1540.25cm 2 ,30μm<H1≤40μm; (3)270mg / 1540.25cm 2 <CW≤400mg / 1540.25cm 2 ,40μm<H1≤80μm。 5. The pole piece according to claim 1, characterized in that: The active material layer includes a binder. Based on the total weight of the active material layer, the weight percentage of the active material is La, and the weight percentage of the binder is Lb. La satisfies: 94% ≤ La ≤ 98.6%, and Lb satisfies: 0.3% ≤ Lb ≤ 2%.
6. The pole piece according to claim 5, characterized in that: The electrode tab satisfies one of the following conditions: (1) 94% ≤ La ≤ 97.6%, 0.5% < Lb ≤ 2%, 40μm < H ≤ 80μm; (2) 94% ≤ La ≤ 97.6%, 0.3% < Lb ≤ 0.5%, 20μm < H ≤ 40μm; (3) 94% ≤ La ≤ 97.6%, 0.1% ≤ Lb ≤ 0.3%, 3μm ≤ H ≤ 20μm.
7. The pole piece according to claim 5, characterized in that: The electrode tab satisfies one of the following conditions: (a) 97.6% < La ≤ 98.6%, 0.7% < Lb ≤ 1.2%, 40μm < H ≤ 80μm; (b) 97.6% < La ≤ 98.6%, 0.5% < Lb ≤ 0.7%, 20μm < H ≤ 40μm; (c) 97.6% < La ≤ 98.6%, 0.3% ≤ Lb ≤ 0.5%, 3μm ≤ H ≤ 20μm; (d) 98.6% < La ≤ 99.2%, 0.6% ≤ Lb ≤ 1.2%, 3μm ≤ H ≤ 20μm.
8. The pole piece according to claim 1, characterized in that: Along the thickness direction of the electrode tab, the radius of the positive projection of the convex portion is R. Among them, the convex portion has a sharpness S, and S = H / R. The electrode tab satisfies at least one of the following conditions: (1) 0μm < R ≤ 133μm; (2)0.4≤S≤0.6。 9. The pole piece according to claim 1, characterized in that: Along the thickness direction of the electrode tab, the radius of the positive projection of the convex portion is R. The electrode tab satisfies at least one of the following conditions: (1) The center distance between two adjacent convex portions is L, and 2 ≤ L / R ≤ 3; (2) In the unit area of the electrode tab, the total area ratio of the positive projection of the convex portion is M, and 40% ≤ M ≤ 80%.
10. An electrode assembly, characterized in that: The electrode assembly includes a separator and a plurality of electrode tabs. The separator is sandwiched between two electrode tabs with opposite polarities, and at least one of the plurality of electrode tabs uses the electrode tab described in any one of claims 1-9.
11. A battery, characterized in that: Including: A housing; And the electrode assembly described in claim 10, and the electrode assembly is disposed in the internal space of the housing.
Citation Information
Patent Citations
Electrochemical device and electronic device
CN113348570A
Electrode piece, electrode assembly and battery
CN117637990A
Electrode piece, electrode assembly and battery
CN117637991A
Positive electrode sheet, electrochemical device, and electronic device
WO2024138560A1
Negative electrode active material, secondary battery, and electronic apparatus
WO2024178610A1
Cited By
Electrode sheet, electrode assembly and battery
WO2026149505A1